A homogeneous mixture has the same uniform appearance and composition throughout. Many homogeneous mixtures are commonly referred to as solutions. A heterogeneous mixture consists of visibly different substances or phases. The three phases or states of matter are gas, liquid, and solid.
Answer: Convenience sample.
Step-by-step explanation:
Convenience sample is also known as grab or accident or opportunity samples. It is a example of non probability sample that involves selecting of subjects because of the proximity, convenience and accessibility a researcher as to them. This type of samples are not reliable for data gathering when it involves a very large sample space, let's say a global audience.
Answer:
(a) b = (4/7)c
(b) Bill: 40 shingles/hour; Chip: 70 shingles/hour
Step-by-step explanation:
Let b and c represent Bill's and Chip's rates in shingles per hour, respectively. Then we have ...
7b = 4c
c - b = 30 . . . . shingles per hour difference in rates
(a) Bill's rate in terms of Chip's rate can be found by dividing the first equation by 7
b = (4/7)c . . . . . Bill's rate is 4/7 of Chip's rate
__
(b) To find the rates, we can multiply the second equation by 7 and substitute using the first equation:
7c -7b = 210
7c -4c = 210
c = 210/3 = 70
b = (4/7)(70) = 40
Bill's rate is 40 shingles per hour; Chip's rate is 70 shingles per hour.
Answer: If you're looking for the value of x, it's 1.
Step-by-step explanation:
Add the numbers. x-10-2x+7=8+x-10-3x--->x-3-2x=8+x-10-3x
Combine like terms. x-3-2x=8+x-10-3x ---> -x-3=8+x-10-3x
Subtract the numbers.-x-3=8+x-10-3x---> -x-3=-2+x-3x
Combine like terms. -x-3=-2+-3x---> -x-3=-2-2x
Rearrange terms. -x-3=-2-2x---> -x-3=-2x-2
Hope that helps!
Answer:
It has no solution because, 14x cancels out -14x when you move the variables to the left and leaves the equation as 0 = -12, however we know that 0 does not equal -12 which means this solution is false; therefore this equation has no solution since 0 does not equal -12.
Step-by-step explanation:
5 - 4x - 7 - 10x = -8x - 4 - 6x - 10 (Given)
-2 - 14x = -14x - 14 (Combine like terms)
0 = -12 (Move variables(x) to the left and the constants to the right)